Anaesthetic and perioperative management of a dog with biventricular congestive heart failure and advanced second‐degree atrioventricular block. Issue 3 (26th May 2021) - Foster, Andrew; Seo, Joonbum; Veres‐Nyéki, Kata
Abstract: A 7‐year‐old male neutered Cocker Spaniel presented with a 6‐hour history of severe tachypnoea. Cardiac evaluation revealed advanced second‐degree atrioventricular block (2AVB) and biventricular congestive heart failure (CHF). Due to concerns of impending respiratory arrest, mechanical ventilation (MV) and emergency transvenous pacemaker implantation were planned. General anaesthesia was achieved using methadone premedication, midazolam and etomidate induction and isoflurane in oxygen maintenance. On intubation, large volumes of serosanguinous fluid poured from the airway with haemoglobin oxygen saturation (SPO2 ) reading 10%. Suctioning of the airway and initiation of MV improved SPO2 to 85%. Temporary cardiac pacing was achieved with transthoracic pacing pads. Following uneventful pacemaker implantation, the dog continued on MV for 12 h with gradual resolution of pulmonary oedema assessed using serial thoracic ultrasound. The dog was successfully discharged 24 h later. This report highlights anaesthetic considerations and management of a critically ill bradycardic dog, with biventricular CHF.